Toward a green-cultural criminology of "the Rural" - Brisman, Avi (Critical criminology, 2014)
There are many connections between the various strands of critical criminology. Previously, we highlighted common issues between green and cultural criminology, while also noting some of the ways that each perspective could potentially benefit from cross-fertilization (Brisman and South in Crime Media Cult 9(2):115-135, 2013, Green cultural criminology: constructions of environmental harm, consumerism and resistance to ecocide. Routledge, Oxford, 2014; McClanahan in Crit Criminol. doi:10.1007/s10612-014-9241-8, 2014). In this article, we extend our analysis to consider green, cultural and rural criminologies through the exposition of several key issues, including "the rural" as local context in which exploitative global forces may exercise power; agribusiness and the food/profit chain; farming and the pollution of land, water and air; and finally, cultural/media images and narratives of rural life. We focus more specifically on this final intersectionality through an analysis of Jonathan Franzen’s novel Freedom (2010), analyzing his depictions of rural people, environmental activists, and the rural environment through the issue of mountaintop removal. We conclude our article by identifying several examples of key directions in which the intersectionality of green, cultural and rural criminologies might proceed, including trafficking and abuse of farmworkers, harms associated with the cultivation of quinoa, and a critical interpretation of media and popular narrative depictions of environmental issues within rural contexts.